The comparison of spiritual well-being and empathic tendencies in midwifery students: A cross-sectional study from Turkey - Handan Ozcan; Yeliz Dinçer; Büşra Poturoğlu; Sümeyyenur Kaya (Heliyon, 2024)
This study aimed to investigate the relationship between spiritual well-being and empathic tendencies of midwifery students and the affecting factors. The sample of this descriptive-correlation type study, one of the descriptive research methods, included 237 midwifery students. The data were collected using the Descriptive Information Form, the Empathic Tendency Scale, and the Spiritual Well-Being Scale. Empathic tendency was higher among those who chose the midwifery department voluntarily, those who liked the department, those who felt that the department was suitable for them, those who participated in social and scientific activities, those who wanted to progress in the profession, those who wanted to work in the field and those who followed publications related to the field; Spiritual well-being was higher among those who felt that the department was suitable for them, those who participated in social and scientific activities, those who wanted to progress in the profession, those who participated in activities that provided the development of the profession, those who wanted to work in the field and those who followed publications related to the field. It was determined that the empathic tendencies and spiritual well-being of midwifery students were at a moderate level, and as a result of the comparison of Empathic Tendency Scale and Spiritual Well-being scale scores, there was a significant positive relationship between them.